Coping strategies among adolescents and young adults living with HIV/AIDS in Accra-Ghana - Selom Dake; Harriet Affran Bonful; Vincent Ganu; Peter Puplampu; Alexander Asamoah; Hannah Ama Arthur; Linus Mwintuu; Emmanuel Asampong; Irene A. Kretchy; Adote Anum (BMC, 2023)
Abstract Background Living with HIV/AIDS is remarkably stressful and has an adverse effect on one's physical and mental health. In Sub-Saharan Africa, the introduction of highly active anti-retroviral therapy has led to an increased number of children with perinatal acquired HIV who are living into adolescence and adulthood. Developing strategies to cope with HIV becomes imperative, especially among these adolescents. The study determined the factors that influence coping strategies among adolescents living with HIV. Methods An analytic cross-sectional design was used. A total of 154 adolescents aged 10-19 years living with HIV were systematically sampled at the Fevers Unit of Korle Bu Teaching Hospital from June to December, 2021. The adolescent version of the KidCope tool was used to assess the choice of coping strategies. Stata 16 was used to determine associations between independent variables and the coping strategies identified. Only variables that were significant at p = 0.1 or less in the crude model were used to run the adjusted regression model. The level of significance was set at p = 0.05 with a 95% confidence interval. Results The mean age of participants was 19.2 ± 0.45 years with 51.9% (80/154) of participants being males. A majority, 57.1% of the participants employed positive coping strategies with 87.0% (135/154) using cognitive restructuring strategy. In an adjusted linear regression model, participants coping strategies were significantly associated with their educational level (p = 0.04) and presence of both parents as caregivers (p = 0.02). Conclusion Participants largely adopted positive coping strategies in managing the disease. Factors that influenced the choice of coping strategies were higher levels of education and the presence of both parents as caregivers. The importance of a good social support structure and pursuing further education needs to be emphasized in counselling adolescents living with HIV as it promotes the choice of positive coping strategies.